Tropospheric radiative forcing from El Chichón and Mt. Pinatubo: theory and observations - Dutton, Ellsworth G., author; Cox, Stephen K., author (Colorado State University. Libraries, 1995)
The possibility of volcanic effects on global and regional climate variables has had a long history of speculation, correlative study, and proposed physical mechanisms. The potential for widespread surface cooling following the extensive spreading of long-lived stratospheric aerosols following major volcanic eruptions is based on the partial blocking of solar radiation incident at the top of the troposphere. Relatively simple physical mechanisms oppose this potential for cooling: dominant forward solar scattering and absorption of outgoing infrared radiation by the aerosols. More complex considerations are the spatial and temporal variations of the distributed aerosol and its optical and physical properties; potential for water/ice cloud modification by the volcanic particles; surface albedo, water vapor, and cloud feedbacks to a temperature change; the role of the oceans in a large-scale radiatively forced temperature variation; possible circulation modifications; and other forced and· random variations in climate. In the current work, rigorous radiative transfer calculations relative to a subset of the above considerations are carried out and compared to observational data to examine deterministic volcanic effects on climate. Specifically, zonally resolved volcanic radiative forcing at the tropopause, and other levels, is computed from the best available information on the spatial and temporal distribution of volcanic aerosols from two recent eruptions, El Chichon (Mexico, 1982) and Mt. Pinatubo (Philippines, 1991). Accuracy of the radiative calculations is partially verified with surface- and satellite-based irradiance observations. Maximum global seasonal-mean radiative forcings of -4.5 and -2.2 W m-2 are calculated following the Mt. Pinatubo and El Chichon eruptions, respectively. Within hemisphere irradiance gradient anomalies of up to 16% at the tropopause are calculated for the second N. Hemisphere summer following the eruptions. The computed radiative forcing is applied to a simple hemispheric tropospheric temperature change model, assuming constant cloudiness and surface albedo, in an effort to explain observed global temperature records (NOM Microwave Sounding Unit) following the two eruptions. Excellent agreement is seen between explained (modeled) and observed global and hemispheric temperature changes after the Mt. Pinatubo eruption, but not following that of El Chichon. Details of this work and some discussion of the results are given. A simple parameterization of the radiative forcing calculations is given that may prove useful in higher spatial and temporal resolution investigations.
September 1994.
Also issued as Ellsworth G. Dutton's dissertation (Ph.D.) -- Colorado State University, 1995.
Keywords: Weather -- Effect of volcanic eruptions on; Atmospheric radiation